Moses As Figure of the Pope: I. The Papal centaur in Machiavelli’s Prince - Lettieri, Gaetano (De Medio Aevo, 2023)
The appropriation the Roman Popes made of the theological-political figure of Moses is a powerful and pervasive dispositive, the correct reading of which is essential in determining the actual historical and ideological context of Machiavelli’s Prince. The essay examines the figure of Moses in key points of the treatise, decripting Machiavelli’s ambiguous, secularizing and courtly intentions.